Compact quotients of Cahen-Wallach spaces - Kath, Ines; Olbrich, Martin, 1963- (Memoirs of the American Mathematical Society, 2019)
Indecomposable symmetric Lorentzian manifolds of non-constant curvature are called Cahen-Wallach spaces. Their isometry classes are described by continuous families of real parameters. We derive necessary and sufficient conditions for the existence of compact quotients of Cahen-Wallach spaces in terms of these parameters.